Sleep quality in university students during the covid-19 pandemic: literature review (Research, Society and Development, 2022)
This literature review sought to assess the impact of the pandemic on the quality of sleep of college students. Searches were performed in the Biblioteca Virtual de Salud and Periódicos CAPES between August and September 2021, using the following descriptors: (sleep) and (“college student” or undergraduate) and (covid-19 or covid or pandemic). Measures to restrict the contagion of the disease resulted in negative and significant impacts on the quality of sleep of university students. The results also revealed insomnia as a significant predictor of stress, anxiety and depression, as well as anxiety and depression were predictors of poor sleep quality, confirming the relationship between mental health problems and sleep problems. Studies evaluating the impact of the use of electronic devices and cognitive aspects related to sleep were not found, suggesting new research opportunities. The lack of studies on the relationship between sleep and the use of electronic devices and the length of exposure to screens, cognitive impacts on learning due to problems with sleep and physical activity as a protective factor for the maintenance of sleep quality seem to indicate possibilities for further research.